1989
DOI: 10.1063/1.456495
|View full text |Cite
|
Sign up to set email alerts
|

A reevaluation of the viscosity exponent for binary mixtures near the consolute point

Abstract: A reevaluation of the critical exponent of the viscosity anomaly for binary mixtures close to the consolute point is presented. Using published data we make a systematic, consistent study in which corrections due to shear gradients and frequency effects are included and the effect of the functional form for the background viscosity is critically examined. The result is that the value of the exponent is generally found to be larger than reported and larger than the most recent theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…A review of experimentally determined values of z, has shown that a large number of experimental data are consistent with the theoretical value of z,=0.065 [3,4]. Equation(3) represents the asymptotic behavior of the viscosity near the critical temperature.…”
supporting
confidence: 51%
“…A review of experimentally determined values of z, has shown that a large number of experimental data are consistent with the theoretical value of z,=0.065 [3,4]. Equation(3) represents the asymptotic behavior of the viscosity near the critical temperature.…”
supporting
confidence: 51%
“…where Q is a system-dependent amplitude and where z = 0.063 is a universal critical exponent [58][59][60].…”
Section: Excess Thermal Conductivitymentioning
confidence: 99%
“…Most available methods for measuring the dynamic viscosity entail introducing corrections in experimental viscosity values in order to obtain accurate g values [13]. Such corrections are based on OxtobyÕs theory [14,15] and are strongly dependent on n þ 0 , so using inaccurate values of this quantity can lead to spurious viscosity data in the immediate vicinity of the critical point.…”
Section: Introductionmentioning
confidence: 99%